2021
DOI: 10.1016/j.bja.2020.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Pain and Addiction Interdisciplinary Network (PAIN): consensus recommendations for perioperative management of cannabis and cannabinoid-based medicine users by a modified Delphi process

Abstract: In many countries, liberalisation of the legislation regulating the use of cannabis has outpaced rigorous scientific studies, and a growing number of patients presenting for surgery consume cannabis regularly. Research to date suggests that cannabis can impact perioperative outcomes. We present recommendations obtained using a modified Delphi method for the perioperative care of cannabis-using patients. A steering committee was formed and a review of medical literature with respect to perioperative cannabis us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 73 publications
1
25
0
Order By: Relevance
“…A recent consensus-based guideline recommended reducing cannabinoid use 7 days prior to surgery (to less than 1.5 g/day of smoked cannabis, 300 mg/day of CBD oil, 20 mg/day of THC oil) while cautioning not to attempt any tapering strategies within 6 days of elective surgery and not to attempt tapering a day prior to surgery. 115 Contrary to this recommendation, recent reviews of perioperative cannabinoids recommended cessation 72 hours prior to surgery. 84 94 An even more conservative recommendation was recently provided, in which the authors recommended up to 10 days of cessation of oral cannabis consumption.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent consensus-based guideline recommended reducing cannabinoid use 7 days prior to surgery (to less than 1.5 g/day of smoked cannabis, 300 mg/day of CBD oil, 20 mg/day of THC oil) while cautioning not to attempt any tapering strategies within 6 days of elective surgery and not to attempt tapering a day prior to surgery. 115 Contrary to this recommendation, recent reviews of perioperative cannabinoids recommended cessation 72 hours prior to surgery. 84 94 An even more conservative recommendation was recently provided, in which the authors recommended up to 10 days of cessation of oral cannabis consumption.…”
Section: Original Researchmentioning
confidence: 99%
“…Other human studies have found altered gamma neural oscillations in cannabis users, but it remains unclear how those changes would affect anesthetic management. 189 190 Finally, in their consensus recommendations on the perioperative management of cannabis, Ladha et al 115 suggested giving 'extra consideration to greater depth of anesthesia during induction and maintenance of anesthesia' in cannabis users. They also stated that acutely intoxicated cannabis users might have lower anesthetic requirements and recommended the use of intraoperative electroencephalogram (EEG) monitoring.…”
Section: Question 5: Should the Intraoperative Doses Of Anesthetics A...mentioning
confidence: 99%
“…For patients whose procedure is scheduled in more than 7 days, cannabis tapering or cessation can be considered based on amount and frequency consumed. However for patients for which surgery will occur in less than 1 day, weaning or cessation is not recommended due to risk of cannabis withdrawal and/or increased anxiety or pain [ 73 ]. In cases of intermediate use (1–6 days) non-toxic patients may be able to proceed to endoscopy on a case-by-case basis while planning for the above-mentioned considerations associated with use.…”
Section: Discussionmentioning
confidence: 99%
“…67,68 Interestingly, patients on cannabinoids may have higher tolerance to opioids and NSAIDs, requiring higher doses. 69 Addressing patients' psychological comorbidities may also play a key role within a multifaceted approach to PPP prevention after cardiac surgery. Patients may present with preexisting psychological risk factors for the development of chronic pain including anxiety, depression, posttraumatic stress disorder, and pain catastrophizing.…”
Section: A Team Approachmentioning
confidence: 99%
“… 67 , 68 Interestingly, patients on cannabinoids may have higher tolerance to opioids and NSAIDs, requiring higher doses. 69 …”
Section: Prevention Of Pppmentioning
confidence: 99%